INVESTIGATIONS WATER MANAGEMENT AND WATER QUALITY IN PICOS/ PIAUÍ AND TAUÁ /CEARÁ WITHIN THE BILATERAL WAVES PROGRAM IN NORTHEAST BRAZIL - Susanne Voerkelius; Gerold Heinrichs; Margarita M. López Gil; Ligia Alves dos Santos Semrau (Revista Águas Subterrâneas, 2000)
The knowledge on water management, -quality and supply is an essential basis for the evaluation of the potential of regional / national development. Within the project WAVES the investigations of the water quality were performed in surface and ground waters as well as in drinking water supplying systems in urban and rural areas of different municipalities in the region of Picos (Piauí) and Tauá (Ceará). The results show that on principal in the region of Picos the hydrochemical quality does not impose any restriction for the agricultural and drinkingwater use. In Tauá, due to geological conditions part of the water sources can not be used because of the high salt content. The hygienic quality in most of the analyzed samples did not met the requirements of the standards for drinking water. The quality is strongly influenced by different handling caused by the structural differences of the municipalities. In urban areas with water supplying companies the water is chlorinated almost on a routine basis and microbiologically safe, yet containing high concentrations of chlorinated hydrocarbons if surface water is used. The correlation of the results of water quality and structural differences of the municipalities as well as the geological conditions can be used for an up-scaling of the results for those groups in the program WAVES working on a larger scale.